2021
DOI: 10.1017/wet.2021.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of single or sequential POST herbicide applications on seed production and viability of glyphosate-resistant Palmer amaranth (Amaranthus palmeri) in dicamba- and glyphosate-resistant soybean

Abstract: Glyphosate-resistant (GR) Palmer amaranth is a troublesome weed that can emerge throughout the soybean growing season in Nebraska and several other regions of the United States. Late- emerging Palmer amaranth plants can produce seeds, thus replenishing the soil seedbank. The objectives of this study were to evaluate single or sequential applications of labeled POST herbicides such as acifluorfen, dicamba, fomesafen/fluthiacet-methyl premix, glyphosate, and lactofen on GR Palmer amaranth control, density, bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…The experiment provided evidence that Palmer amaranth plants surviving glufosinate were fecund (2,400 to 22,000 seeds plant −1 ) and sequential applications of glufosinate significantly reduced seed production. The fecundity of Palmer amaranth surviving glufosinate applied at the vegetative stage in this research was similar to the fecundity of Palmer amaranth surviving glufosinate and other unrelated herbicides applied in the reproductive stage (de Sanctis et al., 2021; Jha & Norsworthy, 2012; Scruggs et al., 2020).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The experiment provided evidence that Palmer amaranth plants surviving glufosinate were fecund (2,400 to 22,000 seeds plant −1 ) and sequential applications of glufosinate significantly reduced seed production. The fecundity of Palmer amaranth surviving glufosinate applied at the vegetative stage in this research was similar to the fecundity of Palmer amaranth surviving glufosinate and other unrelated herbicides applied in the reproductive stage (de Sanctis et al., 2021; Jha & Norsworthy, 2012; Scruggs et al., 2020).…”
Section: Resultssupporting
confidence: 77%
“…In addition, cross pollination was not controlled in the study; thus, fertilization of female Palmer amaranth surviving glufosinate treatment may be a product of pollen from nontreated male Palmer amaranth in proximity. Similar research conducted did not control for volunteer pollen and the results were similar across tested variables (de Sanctis et al, 2021;Jha & Norsworthy, 2012;Scruggs et al, 2020). However, a true representation of decreased glufosinate susceptibility would be to evaluate biparental crosses of glufosinate-and nontreated plants.…”
Section: Palmer Amaranth Offspring Susceptibility To Glufosinatementioning
confidence: 78%
“…Late-season herbicide applications can reduce seed production (de Sanctis et al 2021;Jha and Norsworthy 2012;Sarangi et al 2020;Scruggs et al 2020). However, no treatments applied to Palmer amaranth after seed development caused a great decrease in seed viability in the present study, although previous research reported that trifluralin applied to cheat seed can reduce emergence by more than 90% (Stone et al 2001).…”
Section: Chemical Inflorescence Treatmentmentioning
confidence: 99%
“…Other research evaluating 2,4-D, dicamba, glufosinate, and glyphosate applied at first female Palmer amaranth inflorescence resulted in decreased seed production but not germination or viability (Scruggs et al 2020). Similarly, registered rates of acifluorfen, dicamba, fluthiacet, fomesafen, glyphosate, and lactofen applied to Palmer amaranth up to 90 cm tall did not affect seed viability but seed production was reduced (de Sanctis et al 2021). Each of these studies evaluated herbicides that were applied before seed maturity.…”
Section: Introductionmentioning
confidence: 99%
“…Dicamba can control 120 annual, 19 biennial, and 65 perennial broadleaf weeds (Anonymous 2020). Growers rely on dicamba for POST broadleaf weed control, including control of glyphosate-resistant Palmer amaranth (Amaranthus palmeri S.Watson) in DGR soybean (De Sanctis et al 2021); however, velvetleaf escape has been observed where dicamba was the only herbicide applied POST (Figure 1). Murphy and Lindquist (2002) reported poor control of velvetleaf with dicamba at 318 g ae ha −1 under field conditions.…”
Section: Introductionmentioning
confidence: 99%